Investigating the Specialty Coffee Industry's Allure for Local and Global Investors - Maspul, Kurniawan Arif; Akrem, Ahmed Mohammed; Sidiq, Ari Rahmana (Jurnal Sosial Sains dan Komunikasi, 2024)
The specialty coffee industry has experienced remarkable growth globally, becoming a prominent trend in various regions. In the Middle East, Saudi Arabia has emerged as a significant player, attracting substantial investor interest in the specialty coffee sector. This article aims to delve deeper into the reasons behind the allure of the specialty coffee industry in Saudi Arabia, highlighting its position as a global trendsetter in the Middle East. Saudi Arabia's rising middle class, cultural attachment to coffee, thriving coffee culture, government support, and export potential contribute to its appeal for investors. Employing a qualitative approach, including interviews, discussions, and literature review, this study provides comprehensive insights into the specialty coffee industry in Saudi Arabia. The findings emphasize the significant potential for long-term growth and profitability, making specialty coffee investments in Saudi Arabia an attractive proposition for local and global investors.